Feeding Patterns of Three Widespread Carnivores—The Wolf, Snow Leopard, and Red Fox—in the Trans-Himalayan Landscape of India - Shrotriya, Shivam; Reshamwala, Hussain S.; Lyngdoh, Salvador; Jhala, Yadvendradev V.; Habib, Bilal (Frontiers in Ecology and Evolution, 2022)
The Trans-Himalayan landscape is an extreme cold desert with limited diversity and a low density of wild prey. The landscape has three widespread carnivores – the wolf Canis lupus chanco, snow leopard Panthera uncia, and red fox Vulpes vulpes – competing for similar prey. We studied predation patterns, dietary competition and niche segregation of three sympatric carnivores in the Indian Trans-Himalayas. The Himalayan or woolly wolf is one of the oldest lineages, and has adapted to extreme cold. We further studied the prey selection of the wolf in the high-altitude environment. We collected 1,600 carnivore scats (wolf= 542, snow leopard= 31, and red fox= 1027), and additional data on 573 snow leopard scats from literature was used in the analyses. We found that livestock was a major contributor to the wolf (56.46%) and snow leopard diet (30.01%). The wolf consumed blue sheep (8.26%) and ibex (3.13%), whereas snow leopard subsisted on blue sheep (30.79%) and ibex (17.15%) among the wild ungulates. The red fox preyed upon small species like pika and marmots (18.85 %); however, livestock carrions (16.49%), fruits and seeds (15.05%), and human-derived material (11.89%) were also consumed frequently. The dietary niche of three carnivore species highly overlapped (Pianka’s index= 0.503, simulated mean= 0.491, p= 0.15) due to livestock. The carnivores segregated their diet in prey items originating from the wild. We tested a relationship in carnivore diet variations and prey/predator functional traits based on RLQ ordination. Predator morphology traits like body size, body weight, and habitat preference significantly affected the prey selection (p < 0.05). The wolf and snow leopard avoided the competition through habitat selection, while the red fox coexisted by exploiting a broader niche. The wolf showed site-specific variation in prey preferences albeit no prey selection at the landscape level (G2= 6.79, df= 12, p= 0.87). The wolf preferred wild prey over domestic species at wild prey rich site. The carnivores in this pastoralist landscape have adapted to exploit livestock resources despite facing persecution. Therefore, managing livestock and simultaneously restoring wild prey is crucial for the conservation of carnivore guild in the Trans-Himalayan ecosystem.